FREQUENCY OF CONSERVATIVELY MANAGED TRAUMATIC ACUTE SUBDURAL HAEMATOMA CHANGING INTO CHRONIC SUBDURAL HAEMATOMA - Ahmed, Ehtisham; Aurangzeb, Ahsan; Khan, Shahbaz Ali; Maqbool, Saadia; Ali, Asghar; Zadran, Khalid Khan; Nawaz, Amir (Journal of Ayub Medical College Abbottabad, 2012)
Background: Traumatic brain injury represents a significant cause of mortality and permanent disability in the adult population. Acute subdural haematoma is one of the conditions most strongly associated with severe brain injury. Knowledge on the natural history of the illness and the outcome of patients conservatively managed may help the neurosurgeon in the decision-making process. Methods: We prospectively analysed 27 patients with age ranges 15-90 years, in whom a CT scan diagnosis of acute subdural haematoma was made, and in whom craniotomy for evacuation was not initially performed, to the neurosurgery department of Ayub Teaching Hospital Abbottabad (2008- 2011). Patients with deranged bleeding profile, anticoagulant therapy, chronic liver disease, any other associated intracranial abnormalities, such as cerebral contusions, as shown on CT, were excluded from this study. All patients were followed by serial CT scans, and a neurological assessment was done. Results: There were 18 male and 9 female patients, Cerebral atrophy was present in over half of the sample. In 22 of our patients, the acute subdural haematoma resolved spontaneously, without evidence of damage to the underlying brain, as shown by CT or neurological findings. Four patients subsequently required burr hole drainage for chronic subdural haematoma. In each of these patients, haematoma thickness was greater than 10 mm. The mean delay between injury and operation in this group was 15-21 days. Among these patients 1 patient required craniotomy for haematoma removal due to neurological deterioration. Conclusion: Certain conscious patients with small acute subdural haematomas, without mass effect on CT, may be safely managed conservatively, but due to high risk of these acute subdural haematoma changing into chronic subdural haematoma these patients should be reinvestigated in case of neurological deterioration. Keywords: Acute subdural haematoma, conservative treatment, traumatic brain injury